2004
DOI: 10.1111/j.1365-2222.2004.01997.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of histamine‐releasing activity of sera from patients with chronic urticaria showing positive autologous skin test on human basophils and mast cells

Abstract: Sera from nearly all ASST-positive patients with CU are able to induce histamine release in vitro. However, the serum from each single patient seems to show its maximal activity on autologous mast cells in vivo, and functional in vitro tests show much variability and seem less sensitive than ASST in the detection of patients with histamine-releasing factors in their blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…The frequency of ASST-positive results varied from 24.7 to 65.5%, in accordance with previous data in the literature [14,15]. The number of patients undergoing ASST varied in the studies from 45 to 228.…”
Section: Resultssupporting
confidence: 78%
“…The frequency of ASST-positive results varied from 24.7 to 65.5%, in accordance with previous data in the literature [14,15]. The number of patients undergoing ASST varied in the studies from 45 to 228.…”
Section: Resultssupporting
confidence: 78%
“…Asero et al [12] have published a comparison between the in vitro histamine-releasing assays on mast cells and basophils and the in vivo technique of ASST in a cohort of patients. They concluded that, although patients with a strongly positive ASST had detectable in vitro histamine-releasing factors, the variability of the in vitro histamine-releasing tests was high, and sensitivity of detection of endogenous-releasing factors was lower than in the in vivo ASST.…”
Section: Diagnosis Of Autoimmune Urticariamentioning
confidence: 99%
“…Further work suggested that, in most sera, functional anti-FcεRIα did not compete with IgE for the receptor at the cell surface, but, in a few patients, competitive binding occurred [7]. Functional anti-FcεRIα in a proportion of patients with chronic spontaneous urticaria has been demonstrated by independent laboratories acting on basophils [8], a rat basophil leukemia cell line [9], and on mast cells [10][11][12].…”
Section: An Endogenous Factor Responsible For Chronic Urticaria In Somentioning
confidence: 99%
“…The basophil histamine release assay (HRA) currently remains the "gold standard" for confirmation of functional antibodies in the serum of patients with CU [9]. The HRA used by some authors is less sensitive than ASST in detection of patients with histamine releasing factors in their blood [10]. Furthermore, HRA is time consuming and cumbersome to perform.…”
Section: Introductionmentioning
confidence: 99%